Nursing manpower forecast for cancer patients. (April 2021) - Chung, Min-Huey; Hung, Kuo-Chen; Chiou, Jeng-Fong; Fang, Hui-Fen; Chiu, Chih-Hao
Highlights: Nursing manpower needed for the cancer disease healthcare will increase continuously in the future. The incoordination between teaching and examination has impact on the nursing manpower supply. By applying traditional fuzzy set to system dynamic, it replaces the definite values with interval values, making the prediction results more flexible. Manpower for cancer medical care demand is calculated. Manpower for cancer medical care supply is estimated through data analysis. Abstract: Background and objectives: This paper presents a dynamic model aimed at predicting nursing manpower requirements for cancer care over the next ten years. The proposed model, based on the Taiwan Health Insurance Database (2000 to 2010), is meant to serve as a reference in establishing policy for government health units. Methods: The proposed prediction model uses fuzzy sets to replace definite values with interval values in order to account for uncertainties in real-world data and enhance the flexibility of prediction results. Results: Our results suggest that the demand for nursing manpower for cancer care will grow steadily in the foreseeable future. The gap between the demand for nursing staff and the supply is expected to peak in 2027. By then, the number of oncologists is expected to reach 7, 083 (54.32% of the total number of in-hospital physicians), but the number of oncology nurses will be less than 26, 297 (56.5% of the total healthcare manpower). It is also expected that there will be fewer than 1, 613 outpatient physicians (71.81% of the total number of physicians) and fewer than 4, 967 outpatient nurses (68.46% of the total nursing manpower). Conclusions: This paper provides a valuable reference for government agencies involved in the nursing manpower planning to improve the quality of nursing care.